# How do you solve #x-3y=4# and #-3x+5y=-14# using substitution?

##### 1 Answer

#### Explanation:

First, we rearrange one of the formulae to give us

Now we can substitute in our value for

Then you expand the bracket and simplify it to find

#-3x + 5y = -14#

#-3 (4+3y) + 5y = -14#

(expand the brackets)

#-12 - 9y +5y = -14#

(simplify the

#-12-4y = -14#

(add

#-4y=-2#

(divide both sides by

#y=-2/-4#

#y = 0.5#

We then substitute the

Then we can use the *other* equation to check our answer.

So we know our answer is right!